Analysis of the Impact of Regulatory Change, Law Enforcement Effectiveness, and Bureaucratic Accountability on Public Service Quality - Loso Judijanto; T. Saiful Basri; Afif Syarifudin Yahya; Kalijunjung Hasibuan (Westscience Press, 2024)
This research investigates the intricate relationships among Bureaucratic Accountability, Impact of Regulatory Change, Law Enforcement Effectiveness, and Public Service Quality through a quantitative analysis employing Structural Equation Modeling (SEM). Utilizing a sample size of 150 participants, the study explores the nuanced interplay of these constructs, providing valuable insights for policymakers and administrators. The measurement model demonstrates robust reliability and validity, while the structural model reveals significant positive associations between Bureaucratic Accountability, Impact of Regulatory Change, Law Enforcement Effectiveness, and Public Service Quality. Demographic variations further enrich the understanding of these relationships. The findings contribute to the discourse on effective governance, emphasizing the pivotal role of transparency, regulatory adaptability, and law enforcement efficiency in shaping public service perceptions. Implications for policy and avenues for future research are discussed.